Gestão documental em meio digital: avaliação de documentos para suporte digital - SOUSA, Larissa de Fátima Durães de (2022)
The present research deals with document management in the digital environment and conceptualizes the origin and context of the development of its practice in the physical environment until its arrival in digital information environments, driven by the vertiginous growth of this new type of support in the most varied spheres of society. Its objective is to analyze the document evaluation function, aimed at digital media. As a theoretical basis, concepts that are closely linked and form the basis of the function were sought, such as: the chain of custody, documentary cycle, theory of value, and temporality table. The justification for this study is characterized by the need for the archivist to act in the face of this new informational technological scenario. This contributes to the development of tools for computerized management systems that meet archival functionalities, ensuring one of the main contributions of the profession, which is to provide broad access to information regardless of the support in which it is inserted for society. The methodological approach is qualitative, seeking to analyze which elements allow the application of the evaluation in digital documents in accordance with the legislation, norms and guidelines of the area that deal with the subject from the bibliographical review. The research universe is aimed at scientific production in the related area, with a sample outlined in the Google Academic, Scielo and Brapci knowledge bases and the results will be demonstrated based on the filtering parameters of publications from the last 7 years. The search terms used will consist of the terms “Evaluation” and “Digital document”.